Airway-centered interstitial fibrosis – an under-recognized subtype of diffuse parenchymal lung diseases - Silbernagel, Edith; Morresi-Hauf, A; Reu, S; King, B; Gesierich, W; Lindner, M; Behr, J; Reichenberger, F (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
Airway centered interstitial fibrosis (ACIF) has been recently suggesed as a rare histological pattern of interstitial lung disease of variable etiology and outcome. It is characterized by fibrosis of the respiratory bronchioles and the peribronchiolar interstitium. We describe the clinical features of 13 patients (7 female, mean age 55 years) with histologically proven ACIF in 12 cases and long-term follow up. In ten patients, exogenous agents could be detected (mould n=5, wood n=2, leather exposure n=1, occupational exposure n=2). Two patients had rheumatoid arthritis and 1 patient suffered from recurrent aspiration. In three patients no associated exposure could be detected. Eight patients were never-smokers, while five were ex- smokers. At time of diagnosis patients presented with a moderate restrictive ventilation impairment and sever reduction in diffusion capacity (VC 61%, TLC 66%, DLCOc-SB 38% pred.). All patients were started on immunosuppressive therapy with steroids which were combined with azathioprine in seven and with mycophenolate mofetil in one patient. Median time of follow up was 52 months (2-127 months). Patients with ACIF due to exogenous agents or associated with RA were stable with immunosuppressive therapy. One patient with idiopathic ACIF showed a progressive deterioration within 29 months despite immunosuppression and died while on a waiting-list for lung transplantation. In our experience ACIF is a rare finding, which is relatively frequently observed in the context of hypersensitivity pneumonitis, aspiration and rheumatoid arthritis, while idiopathic ACIF was a minority. In the majority of patients, ACIF showed a favorable long-term outcome with immunosuppressive therapy.